Asymmetrical side-chain engineering of small-molecule acceptors enable high-performance nonfullerene organic solar cells. (January 2020) - Kan, Bin; Chen, Xuebin; Gao, Ke; Zhang, Ming; Lin, Francis; Peng, Xiaobin; Liu, Feng; Jen, Alex K-Y.
Abstract: Three new small molecules based on the benzo [1, 2-b:4, 5-b']dithiophene (BDT) fused central core with different side-chains, namely DPBDT-4Cl, POBDT-4Cl and COBDT-4Cl, are designed and synthesized to investigate the side-chain effect on the properties of nonfullerene acceptors. DPBDT-4Cl has symmetrical phenylalkyl side-chains on the central BDT unit. In order to narrow the bandgap and reduce the steric hindrance, the phenylalkyl chains are systematically replaced with the flexible electron-donating alkoxy side-chain (POBDT-4Cl) and alkyl side-chain (COBDT-4Cl). As a result, POBDT-4Cl and COBDT-4Cl are characterized with asymmetry-featured side-chains. From DPBDT-4Cl to POBDT-4Cl to COBDT-4Cl, their light absorption abilities, molecular packing behaviors and crystallinity are gradually enhanced. The devices based on these three acceptors all show power conversion efficiencies (PCEs) over 11% with energy loss below 0.55 eV. Compared to DPBDT-4Cl, POBDT-4Cl and COBDT-4Cl obviously exhibit enhanced device performance with improved short-circuit current densities ( J sc ) and fill factors (FFs), which mainly ascribe to their reduced charge recombination and enhanced charge transport. In addition, the COBDT-4Cl achieved a high efficiency of 13.5% with a J sc of 21.8 mA cm −2 and an FF of 0.71. This result is among the best performance obtained from asymmetry-featured small molecules. Graphical abstract: Three small-molecule acceptors with different side-chains are designed and synthesized. Compared to DPBDT-4Cl with symmetrical side-chains, POBDT-4Cl and COBDT-4Cl with asymmetrical side-chains exhibited enhanced device performance due to their better light absorption and enhanced charge transport. The COBDT-4Cl NFA enable device to achieve a high efficiency of 13.5% - one of the best performance obtained from the asymmetrical side-chain small molecules. Image 1 Highlights: Small-molecule acceptors with different side-chains are reported to investigate the side-chain effect on the properties of acceptors. POBDT-4Cl and COBDT-4Cl with asymmetrical side-chains exhibited reduced steric hindrance, better light absorption and enhanced charge transport. The COBDT-4Cl based device achieved a high efficiency of 13.5% - the best performance obtained from acceptors with asymmetrical side-chains.